Effects of Visual Deprivation on Gait Dynamic Stability - Marco Iosa; Augusto Fusco; Giovanni Morone; Stefano Paolucci (The Scientific World Journal)
Vision can improve bipedal upright stability during standing and affect spatiotemporal parameters during walking. However, little is known about the effects of visual deprivation on gait dynamic stability. We have tested 28 subjects during walking under two different visual conditions, full vision (FV) and no vision (NV), measuring their upper body accelerations. Lower accelerations were found in NV for the reduced walking speed. However, the normalized accelerations were higher in the NV than in the FV condition, both in anteroposterior (1.05±0.21 versus 0.88±0.16, P=0.001) and laterolateral (0.99±0.26 versus 0.78±0.19, P<0.001) directions. Vision also affected the gait anteroposterior harmony (P=0.026) and, interacting with the environment, also the latero-lateral one (P=0.017). Directly (as main factor of the ANOVA) or indirectly (by means of significant interactions with other factors), vision affected all the measured parameters. In conclusion, participants showed an environment-dependent reduction of upper body stability and harmony when deprived by visual feedback.